The effect of isolation on the Australian attitude workshop presented by Bloodwood bush band at the National Folk Festival in Queensland Folk Federation collection - Bloodwood (Musical group : Alice Springs, N.T.); Queensland Folk Federation; National Folk Festival 1981: Brisbane, Qld.) (1981)
Folkloric recording.
Bloodwood sing, play and recite poetry: 1. soundcheck -- 2. singing: Billy of tea -- 3. Sweet ladies of Plymouth -- 4. In Tennant bloody Creek -- 5. Moreton Bay -- 6. poetry recitation: To the Gulf / Australia's fag end -- 7. singing: There's no place more Australian -- 8. Queensland whalers -- 9. Stringybark and greenhide -- 10. The shearing is all over -- 11. poetry recitation: Bill -- 12. singing: Lime-juice tub -- 13. Poetry recitation: The bearded men of Federation -- 14. singing: Hey ho ho-bo -- 15. Mock news bulletin -- 16. monologue: It was me -- 17. singing: We've come a long way -- 18. The old bullock dray.
Recordings of folk festivals, workshops, concerts, performances and recitations by various artists collected by the Queensland Folk Federation throughout the mid 1960s to the late 1980s. Included in this collection are select radio folk programmes.
Original recordings held with ScreenSound Australia.
Recorded in April, 1981 at the 15th National Folk Festival at Brisbane, Queensland.
Digital master available
Keywords: Folk music -- Queensland; Folk festivals -- Queensland